2019
DOI: 10.1111/scs.12755
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Kangaroo Mother Care practice implementation and future challenges: an integrative review

Abstract: Background Nurses play a crucial role in Kangaroo Mother Care practice, but their application in specific policies and practices involves challenges. A comprehensive literature review is needed to improve understanding of specific barriers that are most relevant to nurses and the improvement of this practice. This review investigates nurses’ barriers in implementing Kangaroo Mother Care, in order to illustrate directions for future research. Methods This study was based on integrative review method and explori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…One mother in our study did not see or touch her newborn for 30 hours after the birth. Our findings are in accordance with other studies in which unexpected events or critical health conditions related to the mother or the infant resulted in a long separation time ( Maniago et al, 2020 ; Vaerland et al, 2018 ). Maastrup et al (2018) showed the value of experiencing SSC in a case where extremely preterm twins did not survive, indicating “it is important to avoid delaying the initiation of SSC” (p. 551).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…One mother in our study did not see or touch her newborn for 30 hours after the birth. Our findings are in accordance with other studies in which unexpected events or critical health conditions related to the mother or the infant resulted in a long separation time ( Maniago et al, 2020 ; Vaerland et al, 2018 ). Maastrup et al (2018) showed the value of experiencing SSC in a case where extremely preterm twins did not survive, indicating “it is important to avoid delaying the initiation of SSC” (p. 551).…”
Section: Discussionsupporting
confidence: 93%
“…One mother in the TC group considered that TC might be a safer intervention than early SSC due to the risk of unexpected infant instability during the early SSC session. Safety concerns have been shown in other studies as obstacles to early SSC ( Hubbard & Gattman, 2017 ; Maniago et al, 2020 ). However, all mothers who received early SSC in our study described a feeling of safety by mentioning crucial aspects such as adequate information, monitoring, and the constant presence of health professionals who followed a detailed early SSC procedure and were close by the whole time.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations